(untitled) (GYMNASIUM, 2008)
The organized and scheduled character of the education is demonstrated by the fact that the developing strategy is programmed depending on the social command and psyhchopedagogical outlines. The educational projection corresponds to this aim, process which includes a series of operations which specify the educational finalities.